Experimental study of an in-service spread slab beam bridge. (15th November 2016) - Jiang, Dongqi; Terzioglu, Tevfik; Hueste, Mary Beth D.; Mander, John B.; Fry, Gary T.
Highlights: An in-service prestressed concrete spread slab beam bridge was statically and dynamically tested. Load distribution behavior of the spread slab beam bridge system was studied. Effects of integrally cast sidewalk and guardrail elements were evaluated. The dynamic responses of the specific bridge system were investigated. A finite element model was developed for the tested bridge. Abstract: A new class of spread slab beam bridges has recently been developed and implemented in Texas. Due to the absence of appropriate design guidelines, moment and shear design actions have been based on those used for spread box beam bridges; however, their applicability remains in question. To develop new criteria, the load distribution behavior of this new bridge system is investigated. Comprehensive static and dynamic tests are performed on an in-service spread slab beam bridge located on US 69 in the city of Denison, Texas. Various experimental methods are used to infer the moments and shears resisted by individual beams that arise from a heavily loaded truck. Experimentally derived load distribution factors (LDFs) are compared with refined finite element model predictions. Satisfactory agreement is obtained. The experimental test results indicate that the existence of a sidewalk and guardrail markedly stiffens the structure leading to higher than expected moment values. The observed bridge responses under moving dynamic loads exceed the present design specifications impact factor of 33%. Thus, for service load design it is recommended the allowable tensile stress be slightly reduced.